Analysis Method at Bertrand Russell - Alaa Aldeen, Ghssan (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The thing that distinguishes Russell from others philosophers of analysis in the 20th century, as Moore and Wittgenstein, maybe the fact that he aimed to establish the method of philosophical analysis on scientific, logical, and mathematical foundations. He got it from the great development at the field of these sciences, which he credited for establishing its origins along with famous mathematicians of his time such as, Peano, Frege and many others. This has frankly made him the pioneer of the philosophical analysis in the 20th century. After that, Russell began to analyze words and reconstruct facts and issues in the terms of logical understanding, which he has given intensive care. He also tried to break down issues to their primary elements. This way, he was able to eliminate false meaningless issues replacing them with the real issues which deserve attention through the use of Occam’s razor. Russell considered it as the essential tool of analysis for the separation between the philosophical issues and these likes. However the critics of his philosophy found that his analytical method includes other forms of tacit analysis. He has responded to some of these idealism and metaphysical criticisms, while he ignored other criticisms, because they are very close to the headlines of his analytical method and are therefore not far from it.